2020
DOI: 10.33448/rsd-v9i9.6813
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory pathways involved in adipose tissue hypertrophy and the effect of Acai (Euterpe oleracea Martius) on the modulation of this process: a review

Abstract: Adipose tissue plays an important role in chronic inflammation and the presence of bioactive compounds in food has been widely discussed as a means of prevention and treatment of various pathological conditions. The aim of this review is to promote an overview and elucidate pathways involved in the chronic inflammatory process triggered by adipose tissue hypertrophy and to discuss data related to the use of Acai in the modulation of inflammation. Initially, a narrative review was carried out on metabolic and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…They suggested that regular açaí intake can positively influence endogenous antioxidant processes, thereby protecting cells from oxidative damage. Moreover, açaí consumption can affect lipid metabolism, displaying beneficial effects on LDL-c and HDL-c control ( Aliaño-González et al, 2020 , Liz et al, 2020 , Machado et al, 2019 , Magalhães et al, 2020 , Silva et al, 2019 , Silva et al, 2020 , Souza et al, 2020 ). Furthermore, when studying the biological properties of the açaí oil, several researchers found a powerful in vitro antioxidant activity from it as well as a great content of phenolic compounds non-anthocyanins, which could be potentialized when encapsulated into micro- or nanoparticles to a controlled release in specific targets ( Pacheco-Palencia et al, 2008 , Rufino et al, 2011 , Teixeira-Costa et al, 2020 ).…”
Section: Potential Effects Of Amazonian Fruits and Oilseeds To Streng...mentioning
confidence: 99%
“…They suggested that regular açaí intake can positively influence endogenous antioxidant processes, thereby protecting cells from oxidative damage. Moreover, açaí consumption can affect lipid metabolism, displaying beneficial effects on LDL-c and HDL-c control ( Aliaño-González et al, 2020 , Liz et al, 2020 , Machado et al, 2019 , Magalhães et al, 2020 , Silva et al, 2019 , Silva et al, 2020 , Souza et al, 2020 ). Furthermore, when studying the biological properties of the açaí oil, several researchers found a powerful in vitro antioxidant activity from it as well as a great content of phenolic compounds non-anthocyanins, which could be potentialized when encapsulated into micro- or nanoparticles to a controlled release in specific targets ( Pacheco-Palencia et al, 2008 , Rufino et al, 2011 , Teixeira-Costa et al, 2020 ).…”
Section: Potential Effects Of Amazonian Fruits and Oilseeds To Streng...mentioning
confidence: 99%